1999
DOI: 10.1115/1.2832688
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Circular Braiding Process, Part 2: Mechanics Analysis of the Circular Braiding Process and Experiment

Abstract: The final structure of a braid is a consequence of force interactions among yarns in the convergent zone. In Part 1, the influence of friction forces on the final braided structure was discussed via kinematic analysis. A transformation from a 3-D cone to a 2-D plane was made for the mechanics analysis. A mechanics model is proposed in this paper to determine the braid angle by considering interlacing forces. Equilibrium equations for the braiding process are deduced. A Newton-Raphson method is used to solve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 3 publications
2
21
0
Order By: Relevance
“…Zhang et al [4,5] reported that the discrepancy between kinematic models and experiments increases with the friction and the number of spools. They modeled the axisymmetrical braiding process with a cylindrical mandrel and a 64-carrier machine.…”
Section: Previous Workmentioning
confidence: 99%
“…Zhang et al [4,5] reported that the discrepancy between kinematic models and experiments increases with the friction and the number of spools. They modeled the axisymmetrical braiding process with a cylindrical mandrel and a 64-carrier machine.…”
Section: Previous Workmentioning
confidence: 99%
“…Equations (10) and (11) are the general solutions of the differential equation (9). Using these equations, the braid angle of every point on the mandrel's crosssection can be determined by setting the appropriate boundary conditions.…”
Section: Mandrelmentioning
confidence: 99%
“…Using these equations, the braid angle of every point on the mandrel's crosssection can be determined by setting the appropriate boundary conditions. Solving equation (11) involves the use of powerful mathematical software such as Wolfram Mathematica or Maple, and ultimately leads to an excessively long and complicated solution. So for easier and quicker determination of braid angle, differential equation 9is solved numerically by the Euler method.…”
Section: Mandrelmentioning
confidence: 99%
See 2 more Smart Citations